A Cross-Sectional Evaluation of Dental Professional's Knowledge of Locally Delivered Antimicrobial Agents and their Application in Periodontal Practice - Muzammil Moin Ahmed; Dhafer S Alasmari (Wolters Kluwer Medknow Publications, 2023)
Introduction: Dentists must employ locally delivered antimicrobial agents (LDAs) in a way that is in line with current recommendations from the scientific literature and the guidelines set by professional organizations. Considering the dearth of research on this topic, it is not known what strategies are adapted when using LDAs in their periodontal practice. So, the purpose of this research was to investigate how LDAs are utilized by dental professionals in their distinct periodontal practices. Materials and Methods: This cross-sectional study used a closed-ended questionnaire. Dental professionals received electronic copies of the eight-item questionnaire. The questionnaire assessed the relevance of LDAs, how frequently they are used, which ones are used most, the number of patients who receive them, their understanding of pharmacological activities, and their knowledge of current treatment guidelines. The questionnaire's validity and reliability were evaluated before being presented to participants. Using the Statistical Package for the Social Sciences (SPSS), the input was analyzed. Results: A total of 120 dental professionals, with an average age of 34.7 years, answered the questionnaire. Half of these individuals have no history of ever using LDAs. The most frequent LDA used in its different forms was chlorhexidine gluconate (CHX), followed by tetracycline. The majority of participants placed LDAs (80%) in less than 10 patients. Less than half acknowledged the different LDAs and their pharmacological activities. Not even 70% of clinicians were up-to-date on the current European Federation of Periodontology (EFP) guidelines. None of the participants discounted the significance of LDAs in periodontal care. Conclusion: Dental professionals regard LDAs as essential to periodontal therapy. Yet, they lacked knowledge about general, pharmacological, and clinical aspects. The patient experience with LDAs was limited by an inappropriate deployment pattern.